Genomic Perl : From Bioinformatics Basics to Working Code - Rex A Dwyer (Cambridge University Press, 2003)
This introduction to computational molecular biology will help programmers and biologists learn the skills they need to start work in this important, expanding field. The author explains many of the basic computational problems and gives concise, working programs to solve them in the Perl programming language. With minimal prerequisites, the author explains the biological background for each problem, develops a model for the solution, and then introduces the Perl concepts needed to implement the solution. The book covers pairwise and multiple sequence alignment, fast database searches for homologous sequences, protein motif identification, genome rearrangement, physical mapping, phylogeny reconstruction, satellite identification, sequence assembly, gene finding, and RNA secondary structure. The author focuses on one or two practical approaches for each problem rather than an exhaustive catalog of ideas. His concrete examples and step-by-step approach make it easy to grasp the computational and statistical methods, including dynamic programming, branch-and-bound optimization, greedy methods, maximum likelihood methods, substitution matrices, BLAST searching, and Karlin-Altschul statistics.